Molecular identification of Theileria parasites of northwestern Chinese Cervidae - Li, Youquan (BioMed Central, 2014)
BACKGROUND: Theileria and Babesia protozoan parasites are transmitted mainly by tick vectors. These parasites cause heavy economic losses to the live-stock industry, as well as affecting the health of wild animals in parasite-endemic areas. Identification of infectious agents in wild animals is not only crucial for species preservation, but also provides valuable information on parasite epidemiology. Here, we conducted a molecular surveillance study in Northwestern China to assess the prevalence of blood pathogens in cervids. METHODS: PCR analysis and microscopic evaluation of blood smears to detect Theileria- and Babesia-related diseases in Cervidae were conducted, in which 22 blood samples from red deer (n = 22) in Qilian Mountain and 20 from sika deer (n = 20) in Long Mountain were collected and tested for the presence of Theileria and Babesia. The 18S rRNA gene was amplified, and selected polymerase chain reaction (PCR)-positive samples were sequenced for species identification. RESULTS: PCR revealed that 9.1% of the Qilian Mountain samples and 20% of the Long Mountain samples were positive for Theileria uilenbergi; 90.09% of the Qilian Mountain samples (n = 22) were positive for T. capreoli, but all of the Long Mountain samples (n = 20) were negative for T. capreoli; no other Theileria or Babesia species were found. PCR showed that T. uilenbergi and T. capreoli were present in red deer in Qilian Mountain, while only T. uilenbergi was found in sika Deer in Long Mountain. The 18S rRNA gene sequences were aligned against the corresponding GenBank sequences of known isolates of Theileria and Babesia and subjected to phylogenetic analysis. The phylogenetic tree showed that the newly isolated Theileria spp. could be classified as belonging to two clades: one group belonged to the same clade as T. uilenbergi, the other to a clade containing T. capreoli. CONCLUSIONS: Our results provide important data to increase understanding of the epidemiology of Cervidae theileriosis, and will assist with the implementation of measures to control theileriosis transmission to Cervidae and small ruminants in central China.